2019
DOI: 10.1111/hepr.13398
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hepatitis B virus genotypes B and C among chronically hepatitis B virus‐infected patients who received nucleos(t)ide analogs: A multicenter retrospective study

Abstract: Aim Hepatitis B virus genotype B (HBV/B) has been reported to have less risk of liver cirrhosis and hepatocellular carcinoma (HCC), but long‐term observation has rarely been reported. We aimed to clarify the characteristics of HBV/B in nucleos(t)ide analog‐treated patients in an area where HBV/B is more prevalent than in other areas of Japan. Methods A total of 498 chronically HBV‐infected patients treated with nucleos(t)ide analog (lamivudine, entecavir, tenofovir disoproxil fumarate, or tenofovir alafenamide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 47 publications
0
23
0
1
Order By: Relevance
“…In a recent study of patients chronically infected with HBV, HCC incidence was 13.4% at 10 years. In these patients, the incidence of HCC was lower in genotype B (5.3% at 10 years) than in genotype C (18.5% at 10 years) [40]. Another recent study from Japan recorded higher incidence of HCC in genotype B patients compared with genotype C during the first 20 years of follow up; however, the HCC incidence was similar in genotypes B and C, after 20 years [41].…”
Section: Influence Of Hbv Genotypes On Hcc Developmentmentioning
confidence: 70%
See 1 more Smart Citation
“…In a recent study of patients chronically infected with HBV, HCC incidence was 13.4% at 10 years. In these patients, the incidence of HCC was lower in genotype B (5.3% at 10 years) than in genotype C (18.5% at 10 years) [40]. Another recent study from Japan recorded higher incidence of HCC in genotype B patients compared with genotype C during the first 20 years of follow up; however, the HCC incidence was similar in genotypes B and C, after 20 years [41].…”
Section: Influence Of Hbv Genotypes On Hcc Developmentmentioning
confidence: 70%
“…In vitro studies showed that wild-type HBV strains (genotypes A-H) and drug-resistant hepatitis B strains were susceptible to tenofovir alafenamide [56]. In chronically HBV-infected patients treated with different nucleos(t)ide analogues-lamivudine, entecavir, tenofovir (disoproxil fumarate or alafenamide fumarate)-for > 6 months (mean duration of treatment 71 months), patients with genotype B had a significantly higher cumulative rate of HBsAg loss (3.6% at 10 years) than those with genotype C (0.7% at 10 years) [40].…”
Section: Hbv Genotypes and Response To Nucleos(t)ide Analoguesmentioning
confidence: 99%
“…Recently, nucleotide/nucleoside analog (NA) therapy has been widely used, which enables viral suppression and HCC suppression . However, considering the low rate of HBsAg elimination during NA therapy, administration must be continued for a long period of time . Therefore, new therapeutic strategies are required which target HBsAg clearance in patients undergoing long‐term NA administration.…”
Section: Introductionmentioning
confidence: 99%
“…Subgenotypes in HBV genotype C may be associated with the increase of HCC occurrence in patients with HBeAg-positivity [ 40 ]. Patients infected with HBV genotype C progress rapidly to cirrhosis and HCC than patients infected with genotype B in Asia [ 41 , 42 , 43 , 44 ]. Moreover, more patients infected with HBV genotype D developed to cirrhosis and HCC than patients infected with HBV genotype A [ 24 , 45 , 46 , 47 ].…”
Section: Hbv Serotypes and Genotypesmentioning
confidence: 99%